Potential Effectiveness of Goji Berry (Lycium barbarum L.) Extract on Neutrophil Cell Count in Wistar Rats (Rattus norvegicus) Post Tooth Extraction - Shieny Lokanata; Dian Soraya Tanjung; Tengku Annisa Sabila Putri (Jurnal Penelitian Pendidikan IPA, 2026)
Tooth extraction causes tissue injury that triggers an inflammatory response, which is characterized by an increase in neutrophil counts. Although neutrophils play an essential role in the early phase of wound healing, prolonged inflammation may delay tissue regeneration. Goji berry (Lycium barbarum L.) contains various bioactive compounds that have potential anti-inflammatory effects. This study aimed to evaluate the effectiveness of goji berry extract on neutrophil counts in Wistar rats (Rattus norvegicus) following tooth extraction. This study was experimental laboratory research using a post-test group design. A total of 30 male Wistar rats were divided into five groups: negative control, positive control (povidone iodine), and three treatment groups receiving goji berry extract at concentrations of 15%, 30%, and 55%. The extract was formulated as a gel and applied topically to the extraction socket. Neutrophil counts were evaluated on days 1, 3, 5, and 7 through histopathological examination. Data were analyzed using the Shapiro–Wilk test, One Way ANOVA, and the LSD post hoc test. The results showed significant differences in neutrophil counts among groups on days 3, 5, and 7 (p<0.05). The 55% concentration demonstrated the most optimal reduction in neutrophil counts. It can be concluded that goji berry extract has potential as an alternative herbal therapy to support wound healing after tooth extraction.